MLTI EDUCATION IN CHINA: CURRENT SITUATION, CHALLENGES AND COUNTERMEASURES - MA, Qinglin; FU, Xin (Comparative Legilinguistics, 2019)
Based on the Guideline for MTI Training Program established by China National Committee for MTI (Master of Translation and Interpreting) Education, this research makes a successive survey on the status quo of master education of legal translators and interpreters from 2014-2016 to trace the changes and problems revealed in the five major universities of political science and law in China. By comparing and analyzing the information and facts collected on the training target, curriculum setting, teaching staff, platform construction, practical training as well as the employment in those five universities, the authors sort out the diversified advantages and features of the five law schools, and probe into the existing problems and difficulties in common. On the grounds of the survey and interview conducted by the authors in the recent years, the authors put forward the solutions and suggestions on the improvement and future development of Chinese MTI education.